2017
DOI: 10.1016/j.visres.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Attention in natural scenes: Affective-motivational factors guide gaze independently of visual salience

Abstract: In addition to low-level stimulus characteristics and current goals, our previous experience with stimuli can also guide attentional deployment. It remains unclear, however, if such effects act independently or whether they interact in guiding attention. In the current study, we presented natural scenes including every-day objects that differed in affective-motivational impact. In the first free-viewing experiment, we presented visually-matched triads of scenes in which one critical object was replaced that va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 58 publications
3
26
0
Order By: Relevance
“…Since the exact salience definition to be used may depend on the research question, and the development in the field of salience models is still ongoing (see Borji and Itti, 2013 for a review), we refrained from picking one particular measure to be included with the database. Object eccentricity and object size are additional relevant measures to include ( Schomaker et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the exact salience definition to be used may depend on the research question, and the development in the field of salience models is still ongoing (see Borji and Itti, 2013 for a review), we refrained from picking one particular measure to be included with the database. Object eccentricity and object size are additional relevant measures to include ( Schomaker et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…This database includes >800 pictures of objects taken from natural scenes, each rated by 23–47 observers. Visual characteristics of the stimuli such as size and shape were similar across motivational categories, and a recent study using the MONS database demonstrated motivational effects on eye movements when controlling for visual aspects such as stimulus size and visual contrast (Schomaker et al, 2017). All objects and corresponding demographic and rating data are freely available at http://www.allpsych.uni-giessen.de/mons and will soon be uploaded to a permanent public repository.…”
Section: Methodsmentioning
confidence: 97%
“…For example, throughout this manuscript we use the term ''naturalistic'' in order to describe the stimulus scenes in our data set. We use this term in the meaning of ''imitating real life or nature'' in accordance with other literature (Krieger, Rentschler, Hauske, Schill, & Zetzsche, 2000;Torralba, Oliva, Castelhano, & Henderson, 2006;Dorr et al, 2010;Tatler, Hayhoe, Land, & Ballard, 2011;McIlreavy, Fiser, & Bex, 2012;Smith & Mital, 2013;Parks, Borji, & Itti, 2015;Leder, Mitrovic, & Goller, 2016;Ramkumar et al, 2016;Foulsham & Kingstone, 2017;Schomaker, Walper, Wittmann, & Einhäuser, 2017;White et al, 2017). We describe our experimental set-up as naturalistic in part to contrast it with synthetic stimuli with prescribed, isolated eye movements often used for studies involving smooth pursuit (Vidal et al, 2012;Santini et al, 2016): Naturalistic stimuli represent a more complex set of visual inputs that affect oculomotor behavior (Monache, Lacquaniti, & Bosco, 2019), and the idea that the visual system is optimized to efficiently encode the inputs that surrounded our ancestors during evolution is well established (Field, 1987;Atick & Redlich, 1992).…”
Section: Addressing Terminological Ambiguitymentioning
confidence: 99%